How it started, how it evolved: Ukrainian entrepreneurship in Poland - Konrad Pędziwiatr; Hanna Smaliichuk; Inna Voznyuk; Jan Brzozowski (International Entrepreneurship Review)
Objective: This exploratory article analyses the entrepreneurial activities of Ukrainian immigrants in Poland from 2018 to the present. We examine immigrant and refugee entrepreneurship as part of socio-economic adaptation. Despite being the largest immigrant group, Ukrainian entrepreneurship remained limited until 2022. The article highlights three key events-the Revolution of Dignity, the COVID-19 pandemic, and the Russian invasion-and their effects on entrepreneurial activity.